Nation State as Security Provider in Human Security Issue - Made Fitri Maya Padmi (Jurnal Hubungan Internasional, 2015)
Human Security notion is emphasizing on human as the central of security studies, challenging the position of state as the core of security. Some studies are tried to separate the state security and human security, however there are strong connection between these two notions. State has important role in establishing and maintaining the security of its own citizens. Through social contract and social security protection, state are oblige to set the security of its own people as their security goal.